Retain students with hearing loss by providing a few simple services. Issue 1 (13th September 2016) - Williams, Kate
Abstract : Adult students with hearing loss are a diverse group. I know because I am one of them. We vary by age, sex, race, socioeconomic status, and degree of hearing loss. As a result, a one‐size‐fits‐all approach does little to help accommodate us in the classroom, but faculty attitudes about students with hearing loss can be a crucial component of their academic success.